Fully recycled aggregate concrete composite functional additives: Proportioning tests and verification of engineering adaptability - Li, Jianhua; Zhang, Xianjiang; Xu, Xueyong; Wu, Haipeng (Results in engineering, 2025)
•Determine the optimal combined proportion of fly ash and mineral powder.•Propose various methods for compounding polymeric acid-based water-reducing agents.•Provide the preparation method for the pumped FRAC high-performance admixture.•Provide technical support for the commercial application of FRAC. To address the primary demands of resource utilization for construction waste and the sustainable development of the concrete industry, a systematic investigation into the preparation technology and performance optimization of high-performance admixtures for fully recycled aggregate concrete (FRAC) was conducted. Considering the high water absorption rate and complex interfacial characteristics of recycled aggregates, a systematic mix proportion design methodology was developed, and the optimal combination ratio of fly ash and mineral powder was identified. A ternary compound technical route was proposed, wherein ordinary, anti-adsorption, and slow-release polycarboxylate superplasticizers were blended in a ratio of 33 %:33 %:33 %, achieving an initial slump of 220 mm (spread of 650 mm), a 60-minute slump retention rate of 100 %, a water bleeding rate of 3.5 %, and a 28-day compressive strength increase of 35.9 %. Further incorporation of 0.4 % (by Wei’an) water retention agent created a synergistic effect system of ‘water reduction - slump retention - thickening,’ significantly enhancing paste cohesion (segregation rate < 6 %), optimizing pore structure (28-day strength reaching 48.6 MPa), and achieving zero slump loss within one hour. This high-performance admixture was validated in FRAC across C15-C40 strength grades, with results demonstrating that both workability (initial slump of 220 ± 10 mm, 60-minute retention rate > 97.7 %) and mechanical properties (100 % compliance rate of 28-day strength for all grades) met the requirements for pumped concrete. The high-performance admixture technology system developed in this study provides critical technical support for the full-component resource utilization of construction waste and offers significant environmental benefits and engineering application value.